Meta Analisis Pengaruh Makanan Bergizi Terhadap Stunting pada Balita di Indonesia - Sopian Purba; Hardiansjah Sugiana; Fatma Tresno Ingtyas; Laurena Ginting (EduInovasi: Journal of Basic Educational Studies, 2025)
Stunting is a major concern in Indonesia, impacting children's growth, development, and longterm productivity. This study applies a meta-analysis methodology, reviewing 15 relevant studies published from 2019 to 2024, sourced from platforms like Google Scholar, DOAJ, and JSTOR. The research seeks to examine the various factors that contribute to stunting, including exclusive breastfeeding, the appropriate timing for introducing complementary foods (MP-ASI), caloric intake, dietary variety, and the quality and frequency of meals. The findings indicate that exclusive breastfeeding for the first six months, the timely initiation of MP-ASI (at 6–8 months), sufficient caloric intake, and dietary diversity—especially iron-rich foods—are highly effective in reducing stunting. Additionally, a dietary pattern involving more than three meals a day and adequate intake of animal protein is strongly linked to better nutritional status. However, challenges such as limited access to nutritious food and insufficient nutrition education remain significant, particularly for families with lower income. In conclusion, addressing stunting demands a comprehensive approach that includes nutrition education, improved eating habits, and greater access to healthy food, supported by collaboration among families, healthcare professionals, and communities to promote the optimal growth and development of children in Indonesia.